A companion to Mediterranean history - Horden, Peregrine; Kinoshita, Sharon (Wiley Blackwell, 2014)
A Companion to Mediterranean History presents a wide-ranging overview of this vibrant field of historical research, drawing together scholars from a range of disciplines to discuss the development of the region from Neolithic times to the present. Provides a valuable introduction to current debates on Mediterranean history and helps define the field for a new generationCovers developments in the Mediterranean world from Neolithic times to the modern eraEnables fruitful dialogue among a wide range of disciplines, including history, archaeology, ar.